2018
DOI: 10.1093/asj/sjx191
|View full text |Cite
|
Sign up to set email alerts
|

The Ideal Thigh: A Crowdsourcing-Based Assessment of Ideal Thigh Aesthetic and Implications for Gluteal Fat Grafting

Abstract: Characteristics of the ideal thigh include wider thighs with greater horizontal projection, creating a more natural contour from the augmented buttock. These findings represent a paradigm shift from the traditionally assumed preference for slender thighs. Plastic surgeons should carefully consider thigh anatomy in their gluteal augmentation patients, as simultaneous thigh augmentation may lead to a more aesthetically pleasing outcome. Further research is needed into best practices and techniques to attain idea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…For this reason, the thighs and their volumization must be defined because this volumization can occur through implants and fat grafting. 4 , 7 , 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For this reason, the thighs and their volumization must be defined because this volumization can occur through implants and fat grafting. 4 , 7 , 17 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…In their study, Vartanian et al 4 concluded that a wide upper thigh, with an optimal transition from the buttock to the thigh, was the most attractive shape. Therefore, both gluteus and thighs should be increased simultaneously.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 12 However, they have been adapted over time to improve the results of cosmetic surgery of the lower limbs. 13 …”
Section: Discussionmentioning
confidence: 99%